How many orchid species in Costa Rica? A review of the latest discoveries - Bogarín, Diego (2011)
Despite its well-established tradition in botanical exploration, which started in 1846 with the visit of Oersted (1846), Costa Rica is still far from having a complete inventory of its orchidaceous flora. After the publication of the most recent and complete treatment of the family by Dressler in 2003, new species and records have been added on a regular basis to the country’s inventory. Showy, large-flowered species in previously monographed and botanically well-sampled genera such as Brassia, Dracula, Lycaste, Polycycnis, Stanhopea, and Trichopilia have been described, but the vast majority of species are small-flowered and belong to the subtribes Laeliinae, Pleurothallidinae, and Zygopetalinae. Identifying taxa with ephemeral flowers such as Sobralia is problematic, but a large living collection revealed many new species. Previously described species from other countries have regularly been recorded in Costa Rica. These new records have floristic affinities mainly with the floras of Panama, Colombia, Ecuador, and Venezuela. As an example, Acianthera aberrans, Epidendrum scharfii, Epidendrum stellidifforme, Lockhartia chocoensis, Maxillaria bolivarensis, Ornithidium pendulum, Ornithocephalus montealegrae, and Warmingia zamorana have been found in both Costa Rica and Ecuador. The genus Uleiorchis with the Venezuelan species Uleiorchis ulaei, identified in the MO herbarium by Ron Liesner, constitutes an interesting new record in Costa Rica. Maxillaria appendiculoides, first described from Costa Rica, has recently been reported from Ecuador. Campylocentrum tenellum, Lepanthes droseroides, Lepanthes mariposa, and Sobralia bouchei from Panama were also lately collected in Costa Rica. Although much floristic work remains to be completed and the country has significant areas that are poorly sampled, the establishment of large and documented collections of living plants at Lankester Botanical Garden, associated with an increasing access to critical documentation (types and literature), have been the keys to improving our understanding of orchid diversity in Costa Rica and its floristic relationships with other areas.